Qualitative identification of food materials by complex refractive index mapping in the terahertz range. (15th April 2018) - Shin, Hee Jun; Choi, Sung-Wook; Ok, Gyeongsik
Highlights: Terahertz time-domain spectroscopy was applied to qualitative food inspection. Optical parameters were used to differentiate contaminants from food matrix. Foreign bodies such as insects can be clearly identified within food samples. The results demonstrate the feasibility of THz imaging for food inspection. Abstract: We investigated the feasibility of qualitative food analysis using complex refractive index mapping of food materials in the terahertz (THz) frequency range. We studied optical properties such as the refractive index and absorption coefficient of food materials, including insects as foreign substances, from 0.2 to 1.3 THz. Although some food materials had a complex composition, their refractive indices were approximated with effective medium values, and therefore, they could be discriminated on the complex refractive index map. To demonstrate food quality inspection with THz imaging, we obtained THz reflective images and time-of-flight imaging of hidden defects in a sugar and milk powder matrix by using time domain THz pulses. Our results indicate that foreign substances can be clearly classified and detected according to the optical parameters of the foods and insects by using THz pulses.